Periods of periodic homeomorphisms of pinched surfaces with one or two branching points - Gouveia, Márcio R.A. [UNESP]; Llibre, Jaume (My University, 2019)
In this paper we characterize all the possible sets of periods of a periodic homeomorphism defined on compact connected pinched surfaces with one or two branching points.
Keywords: Branched surfaces; Homeomorphisms; Periodic points; Periods